Katie dit it - McDaniel, Becky Bring (New York : Scholastic, 2003)
Katie Did It, is about how Katie's older brother and older sister blame everything on their little sister, Katie. Every time there was something that was supposed to be put away, left open, left on, Katie's older siblings, Jenny and Kris always said "Katie did it!"